Chlorophyll-a and Sea Surface Temperature Analysis Based on Shark Fishing Ground Landed at the Fish Landing Base of Ujong Baroh, West Aceh - Fuadi, Afdhal; Rizal, Muhammad; Kusumayadi, Dimas (Jurnal Ilmiah Perikanan dan Kelautan, 2025)
Graphical Abstract   Highlight Research The number of shark catches in the eastern season was 618. Sharks landed at PPI Ujong Baroh in six species (Sphyma lewini, Alopias pelagicus, Carcharhinus falciformis, Loxodon macrorhinus, Carcharhinus sorrah, and Chiloscyllium punctatum). The distribution of chlorophyll-a parameters in the eastern season ranges from 0.08 to 1.23 mg/m3 with an average value of 0.17 mg/m3. The distribution of sea surface temperature parameters in the eastern season ranges from 27.65 to 30.29oC with an average value of 28.65o Based on linear regression analysis, sharks are most highly influenced by chlorophyll-a oceanographic parameters, namely Loxodon macrorhinus by 72.82%, and sharks are highest influenced by sea surface temperatures, namely Alopias pelagicus by 83.12%.     Abstract  Sharks are top-tier water predators that can maintain marine ecology balance and control the food web. As sharks are at the top of the food chain, their overfishing can disrupt the ecosystem chain. The distribution and abundance of fish in waters can be influenced by several factors of oceanographic parameters, including chlorophyll-a and sea surface temperature (SST). The use of satellite imagery for analyzing chlorophyll-a and SST parameters provides significant results in fisheries oceanographic studies. This study aimed to determine the effect of chlorophyll-a and SST parameters on shark catches. The method in this study was divided into 2 stages, namely taking shark fishing area coordinate data and downloading chlorophyll-a as well as SST satellite image data on the NASA Aqua-MODIS website. The results of the of the analysis of chlorophyll-a distribution in the eastern season ranged from 0.08 to 1.23 mg/m3 with an average value of 0.17 mg/m3, where the highest was 1.23 mg/m3 in September and the lowest was 0.08 mg/m3 in August. The SST distribution ranged from 27.65 to 30.29oC with an average of 28.65oC, the highest was 30.29oC in August and the lowest was 27.65oC in September. Based on the results of linear regression analysis, the highest shark catch was influenced by chlorophyll-a, namely Loxodon macrorhinus shark, by 72.82%, the highest shark catch type was influenced by SPL, namely Alopias pelagicus shark, by 83.12%, and the rest was influenced by other parameters.